2012
DOI: 10.5194/bg-9-2935-2012
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the uptake of carbonyl sulfide (COS) by trees under elevated atmospheric carbon dioxide concentrations

Abstract: Abstract. Global change forces ecosystems to adapt to elevated atmospheric concentrations of carbon dioxide (CO 2 ). We understand that carbonyl sulfide (COS), a trace gas which is involved in building up the stratospheric sulfate aerosol layer, is taken up by vegetation with the same triad of the enzymes which are metabolizing CO 2 , i.e. ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), phosphoenolpyruvate carboxylase (PEP-Co) and carbonic anhydrase (CA). Therefore, we discuss a physiological/bioche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…For example, in previous studies, maximum DMS emissions from Platanus orientalis were found to be 0.42 pmol m À2 s À1 [Geng and Mu, 2006], whereas Hibiscus sp. was reported to emit DMS at a maximum rate of 26 pmol m À2 s À1 [Yonemura et al, 2005].…”
Section: Branch Emissions Of Dms In Relation To Light and Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…For example, in previous studies, maximum DMS emissions from Platanus orientalis were found to be 0.42 pmol m À2 s À1 [Geng and Mu, 2006], whereas Hibiscus sp. was reported to emit DMS at a maximum rate of 26 pmol m À2 s À1 [Yonemura et al, 2005].…”
Section: Branch Emissions Of Dms In Relation To Light and Temperaturementioning
confidence: 99%
“…DMS emission measurements have been reported from soils and leaf litter [Kesselmeier and Hubert, 2002;Lamb et al, 1987;Staubes et al, 1989;Yang et al, 1996] with possible sources from the microbial metabolism of sulfur-containing amino acids [Banwart and Bremner, 1975;Zhang et al, 2004]. Although DMS emissions have also been reported from vegetation [Fall et al, 1988;Geng and Mu, 2006;Jardine et al, 2010a;Kanda and Tsuruta, 1995;Kesselmeier et al, 1993;Yonemura et al, 2005], ecosystem-scale observations remain extremely rare, leaving large uncertainties with regard to the potential importance of terrestrial DMS sources. While plant surveys revealed that most plants studied emit only small amounts of DMS to the atmosphere [Geng and Mu, 2006;Yonemura et al, 2005], large DMS emission rates that increased with light and temperature have been reported from a rainforest tree species in Cameroon [Kesselmeier et al, 1993], agricultural plants like corn [Fall et al, 1988], rice paddies [Zhigang et al, 2008], and the desert plant creosotebush [Jardine et al, 2010a].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the utility of COS as a tracer of GPP depends heavily on the assumption that the flux of COS between the atmosphere and the leaf is one-way and driven by CA activity alone. This assumption has been validated at the leaf level for certain species and environmental conditions (Stimler et al, 2010;Sandoval-Soto et al, 2012). However, recent field studies have shown that COS emissions from wheat leaves may occur during senescence and from deciduous forests during periods of high temperature and drought (Maseyk et al, 2014;Commane et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Vegetation was considered as the main sink for OCS, and the close relationship between OCS uptake and photosynthetic CO2 uptake lead to a considerable increase of the sink strength estimates based on GPP (Sandoval-Soto et al, 2005). Furthermore, changes of the sink strength of vegetation as a response to global change is a matter of discussion (White et al, 2010;Sandoval-Soto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%